2022
DOI: 10.1128/spectrum.01361-22
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Dual-Target Aptima HIV-1 Quant Dx Assay: Comparison between Viral Loads Measured with pol and LTR Targets in the Same Samples

Abstract: The last generation dual-target platforms for quantification of HIV-1 RNA return a single value of viral load (VL) derived from a combined reading of two HIV-1 genome targets. By using a modified version of Aptima software, providing both the VL results obtained from pol and LTR amplification separately, we observed discordant VL results in some samples from HIV-1-infected patients on antiretroviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…We report the case of a chronic PLWH for a long time (>14 years) under suppressive antiretroviral therapy (i.e., pol -based undetected HIV-RNA) showing persistent plasma HIV-RNA detected and quantified only through the LTR -target by the Aptima dual-target assay. Interestingly, other patients show, occasionally or repeatedly over a limited time, VL undetected with the pol -target, but detected with the LTR region above 50 copies/mL by the Aptima dual-target assay [ [3] , [4] , [5] ]. In in-vitro setting [ 5 ], it has been shown that viral genomes detected in plasma samples of PLWH exclusively through the LTR target consist of partial or incomplete genetic elements, unable to encode intact or replication-competent viruses; therefore, these elements cannot trigger new cycles of viral replication nor transmit the infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We report the case of a chronic PLWH for a long time (>14 years) under suppressive antiretroviral therapy (i.e., pol -based undetected HIV-RNA) showing persistent plasma HIV-RNA detected and quantified only through the LTR -target by the Aptima dual-target assay. Interestingly, other patients show, occasionally or repeatedly over a limited time, VL undetected with the pol -target, but detected with the LTR region above 50 copies/mL by the Aptima dual-target assay [ [3] , [4] , [5] ]. In in-vitro setting [ 5 ], it has been shown that viral genomes detected in plasma samples of PLWH exclusively through the LTR target consist of partial or incomplete genetic elements, unable to encode intact or replication-competent viruses; therefore, these elements cannot trigger new cycles of viral replication nor transmit the infection.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, it is crucial to inform clinicians when VL is detected solely with the LTR region. This is because such viremias are unlikely to indicate ART failure, and therefore, the changes in treatment regimen usually recommended in instances of virologic rebound [ 2 , 14 , 15 ] would not be necessary [ [3] , [4] , [5] ].…”
Section: Discussionmentioning
confidence: 99%